Leaf-litter decomposition and nutrient dynamics of five selected tropical tree species - Bhattarai, S.; Bhatta, B. (Banko Janakari, 2020)
Leaf-litter decomposition in terrestrial ecosystems has a major role in recycling the nutrients to the soil. Nutrient dynamics is the way nutrients cycle in an ecosystem. The present study was conducted for five selected tropical tree species viz. Shorea robusta, Ficus hookeri, Mallotus philippensis, Artocarpus lakoocha and Dillenia pentagyna at Hetauda, Makawanpur. This paper aims to determine the litter decomposition rate-constant and nutrient mineralization pattern of the selected species. The litter-bag method was used to assess the decomposition and nutrient dynamics for one year. Both decomposition rate-constant and weight loss were highest for M. philippensis (% weight loss = 73.49; k = 0.33) and lowest for S. robusta (% weight loss = 54.01; k = 0.18). In general, weight remaining showed a strong negative correlation with N and P concentration but a slightly negative with K. However, the remaining weight of litter showed a strong positive correlation with C : N ratio, thus indicating a good predictor of mass loss and mineralization. The study showed that there was no net release of nitrogen during the one-year study period; however, the net P release was found to be highest for S. robusta followed by D. pentagyna and the net K release was highest in F. hookeri followed by A. lakoocha.